2020
DOI: 10.1051/0004-6361/201937122
|View full text |Cite
|
Sign up to set email alerts
|

The Sun at millimeter wavelengths

Abstract: Context. The Atacama Large Millimeter/submillimeter Array (ALMA) started regular observations of the Sun in 2016, first offering receiver Band 3 at wavelengths near 3 mm (100 GHz) and Band 6 at wavelengths around 1.25 mm (239 GHz). Aims. Here we present an initial study of one of the first ALMA Band 3 observations of the Sun. Our aim is to characterise the diagnostic potential of brightness temperatures measured with ALMA on the Sun. Methods. The observation covers a duration of 48 min at a cadence of 2 s targ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
68
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(78 citation statements)
references
References 32 publications
10
68
0
Order By: Relevance
“…Multi-frequency synthesis is employed in order to increase image fidelity, resulting in one brightness temperature map at 2 s cadence corresponding to the central frequency of Band 6 and thus to an effective wavelength of 1.25 mm. We refer to Wedemeyer et al (2020) for more details about data processing with SoAP.…”
Section: Data Reduction and Alignmentmentioning
confidence: 99%
“…Multi-frequency synthesis is employed in order to increase image fidelity, resulting in one brightness temperature map at 2 s cadence corresponding to the central frequency of Band 6 and thus to an effective wavelength of 1.25 mm. We refer to Wedemeyer et al (2020) for more details about data processing with SoAP.…”
Section: Data Reduction and Alignmentmentioning
confidence: 99%
“…The first high-resolution images of the quiet Sun in the millimeter range were obtained by White et al (2006) and Loukitcheva et al (2006) who used the Berkeley-Illinois-Maryland Association Array (BIMA) to obtain ∼ 10 ′′ resolution. With the advent of ALMA a new generation of high-resolution millimeterwavelength images has been forming (e.g., Bastian et al, 2017;Shimojo et al, 2017a,b;Nindos et al, 2018;Yokoyama et al, 2018;Jafarzadeh et al, 2019;Loukitcheva et al, 2019;Molnar et al, 2019;Patsourakos et al, 2020;Wedemeyer et al, 2020) and an example is presented in Figure 2. The figure indicates that the chromospheric network, delineated in the AIA 1,600 Å image, is the dominant structure in the radio images.…”
Section: Imaging Observations Of the Non-flaring Sunmentioning
confidence: 99%
“…Recent studies have shown the potential of ALMA to examine distinct phenomena both in quiet and active regions [31][32][33][34][35][36][37][38][39][40]. In particular, Eklund et al [41] found signatures of shock-wave events in Band 3 (2.8-3.3 mm) observations from December 2016, coming to the conclusion that there are numerous small-scale dynamic structures with lifetimes of 43-360 s present in the ALMA field of view (FOV), with excess temperatures of more than 400 K and a correlation between their occurrence and the magnetic field strength.…”
Section: Introductionmentioning
confidence: 99%